A model of acute kidney injury in mice with cirrhosis and infection. (7th February 2016) - Carl, Daniel E.; Ghosh, Siddhartha S.; Gehr, Todd W.B.; Abbate, Antonio; Toldo, Stefano; Sanyal, Arun J.
Abstract: Background & Aims: Infectious acute kidney injury (AKI) is a life threatening complication of cirrhosis with limited therapeutic options. The aim of this study was to develop a model of infectious AKI in cirrhotic mice. Methods: Cirrhosis was established by intragastric administration of carbon tetrachloride (CCl4 ). Systemic haemodynamics was assessed invasively while cardiac function was assessed by echocardiography. AKI was induced using varying doses of lipopolysaccharide (LPS) titrated to produce 50% lethality. Renal function was assessed from serum creatinine and urine output (UOP). Renal injury was evaluated by urinalysis (proteinuria and casts) and renal histology. These mice were compared to: (i) normal mice, (ii) normal mice + LPS, and (iii) mice treated with CCl4 alone. Results: Cirrhosis with increased cardiac output, decreased systemic vascular resistance, activation of renin–angiotensin–aldosterone axis developed after 12 weeks of CCl4 administration. LPS injection produced a dose‐dependent increase in mortality (33% at 2 mg/kg vs. 80% at 6 mg/kg) without urine (casts or proteinuria) or histological evidence of tubular injury. 2 mg/kg LPS injection produced a rise in creatinine (0.79 ± 0.27 mg/dl in CCl4 +LPS compared to 0.45 ± 0.14 in CCl4 alone, P < 0.05) and a decrease in UOP (0.86 ± 0.4 ml/16 h in CCl4 + LPS compared to 1.70 ± 0.7 ml/16 h in CCl4 mice, P < 0.05). UOP remained low in mice that died while it recovered over 48–72 h in those that recovered. Control mice treated with 2 mg/kg LPS did not experience AKI. Conclusions: Cirrhotic CCl4 treated mice develop functional AKI and mimic most of the features of infectious AKI following LPS injection.